Teacher’s Belief on Teaching Philosophy as Teachers Professionalism Platform - Muhammad Reza Pahlevi; Kusrin kusrin; Acep Bahrum Kamil (Ahmad Dahlan Journal of English Studies, 2020)
This study aims at presenting the teacher's belief on teaching philosophy as a teacher professionalism platform. It explores how the teacher perceives teaching philosophy as a teacher professionalism platform and in what ways teaching philosophy assists the teacher to refine his teaching. The research design of this study is basic interpretative study. It is used to identify the extent to which teaching philosophy is understood and practiced by teachers. There are general pattern findings of this study. The first finding is English teachers' perceived teaching philosophy builds reflective teachers. The second findings refers to reflected activity that copes with the teacher in refining suitable ways in facilitating students to learn. Teaching philosophy potentially assists teachers in teaching by providing various activities. Thus, it supports the teacher to be a professional English teacher.